2011
DOI: 10.1038/bjc.2011.511
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors and histamine-2-receptor antagonists and pancreatic cancer risk: a nested case–control study

Abstract: Background:The relationship between use of proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs) and pancreatic cancer risk has yet to be examined. Data from a range of studies suggest biologically plausible mechanisms, whereby these drugs (or the conditions for which they are prescribed) may affect pancreatic cancer risk. The objective of this study was to investigate the relationship between use of PPIs/H2RAs and pancreatic cancer risk.Methods:A nested case–control study was conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Authors of the Taiwan study concluded that patients with occult colorectal cancer had longstanding reflux or upper gastrointestinal symptoms and concomitantly received PPI treatment. The UK researchers found that PPIs/H2RAs use was not associated with pancreatic cancer risk,43 which is consistent with our finding when limited to the cancer site into pancreatic cancer (Supporting Information Table 2). However, we did not restrict our sample to those with pancreatic cancer as it is difficult to clinically distinguish it from periampullary cancers 18.…”
Section: Discussionsupporting
confidence: 90%
“…Authors of the Taiwan study concluded that patients with occult colorectal cancer had longstanding reflux or upper gastrointestinal symptoms and concomitantly received PPI treatment. The UK researchers found that PPIs/H2RAs use was not associated with pancreatic cancer risk,43 which is consistent with our finding when limited to the cancer site into pancreatic cancer (Supporting Information Table 2). However, we did not restrict our sample to those with pancreatic cancer as it is difficult to clinically distinguish it from periampullary cancers 18.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed a recent study observed no significant association between PPI use and PDAC. (29) A previous study assessing the relationship between H. pylori infection and PDAC demonstrated a statistically significant association. (30) Our data would suggest that the mechanism underlying this association is likely independent of hypergastrinemia.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are the first population-level study with results in accordance with the compelling link between hypergastrinemia and pancreatic cancer seen in vitro and in animal models. Although the only other large epidemiologic study to evaluate the link between PPI therapy and pancreatic cancer found no association (33), the time period during which this study collected data (between 1995 and 2006) may not include the dramatic increase in PPI use seen in recent years. This pervious study also included far fewer cases compared to our study (1,141 compared to 4, 113) (33).…”
Section: Discussionmentioning
confidence: 88%
“…In spite of a highly suggestive mechanism demonstrated in experimental models linking PPI use, and increased gastrin levels to GI cancers, the results of epidemiologic studies have been mixed; several studies showed increased rates of gastric cancer among PPI users (2426) while other studies found no link between acid suppression and gastric cancers (27, 28), colorectal cancer (2932) or pancreatic cancer (33). In this study, we evaluated the impact of PPI use on both the risk of pancreatic cancer and survival after diagnosis in a large, population-based cohort.…”
Section: Introductionmentioning
confidence: 99%